Preclinical Experiential Global Health Leads to Transformative Learning and Long‑term Impact - Marissa Vander Missen; Destiny Resner; Micaela Gaviola; Debra Litzelman; Julia Songok; Jenny Baenziger (Annals of Global Health)
Background: The Slemenda Scholars (SS) program at Indiana University School of Medicine offers preclinical students early exposure to global health through a summer program in collaboration with the Academic Model Providing Access to Healthcare (AMPATH). AMPATH Kenya is a 30‑year partnership between a consortium of US and European universities and Moi University in Kenya that provides sustainable, high‑quality care through medical education, clinical care, research, innovation, and community service. The positive impact of electives during medical students’ clinical years is well documented, but the impact of quality, immersive learning in preclinical years has not previously been studied. Methods: A cross‑sectional survey was administered to past participants of the SS program via e‑mails in 2023. Written narratives about the SS program by participants from 1998 to 2023 were evaluated using qualitative analytic methods. Narratives were obtained via internet search and compiled from open‑ended survey responses. Themes were generated on the basis of a constant comparative method using grounded theory and finalized through an iterative consensus process. Findings: Surveys were distributed to 66 SS alumni. In total, 54 responses were received (81.8% response rate). After excluding incomplete responses, 45 were included in the final analyses (68.2%). Respondents indicated they learned more about themselves (mean 4.9; 5 = strongly agree), global health (mean 5), and medicine (4.9) through the SS program and developed skills, including cultural humility and personal resilience. A qualitative review of 50 narratives identified two major themes: impactful experiences and transformative learning. Conclusions: Preclinical global health experiential learning opportunities are impactful and transformative. Immersive learning expands trainees’ perspectives, promotes the development of relational skills with diverse colleagues, and fosters adaptability. Early, immersive global health exposure within the context of established institutional partnerships affirmed or informed a career addressing health disparities both locally and globally.